Cardiovascular magnetic resonance imaging in heart failure. (3rd April 2018) - Yoneyama, Kihei; Kitanaka, Yuki; Tanaka, Osamu; Akashi, Yoshihiro J.
ABSTRACT: Introduction : Heart failure is a complex clinical syndrome resulting from heart structural remodeling and impaired function in ejecting blood; its incidence is increasing markedly worldwide. The observed variations in the structure and function of the heart are attributable to differences in etiology of heart failure. Cardiac magnetic resonance imaging (CMR) can characterize myocardial tissue, assess myocardial viability, and help diagnose specific cardiomyopathies. The emergence of T1 mapping techniques further improves our knowledge and the clinical assessment of myocardial diffuse fibrosis. Physicians, therefore, must identify the variations using CMR to improve patient's symptoms, survival, and quality of life. Area covered : Current reports regarding CMR and the evidence for heart failure diagnosis and therapy as a potential marker of therapeutic response, including low- and high-risk patients, were reviewed. Literature search was performed using PubMed and Google Scholar for literature relevant to CMR, late gadolinium enhancement, T1 mapping, assessment of fibrosis and remodeling, coronary artery, myocardial infarction, heart failure, and its outcomes. Expert commentary : The authors review current evidence and discuss the potential ability of CMR to guide, diagnose, plan risk strategies, and treat patients with heart failure.